Large-current bus connection terminal and preparation method thereof

By spraying the silver composite coating on the high-current bus connection terminals using cold spraying technology, combined with the ligand effect and shot peening strengthening of palladium/gold nanoparticles, the problem of both anti-sulfurization and conductivity of the silver layer on the high-current bus connection terminals is solved, and efficient corrosion and conductive improvement is achieved.

CN119602007APending Publication Date: 2025-03-11CHINA YANGTZE POWER
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411791449.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to have both anti-sulfurization and conductivity of the silver layer on the high-current bus connection terminals, and the preparation method is limited by the structure, volume and environment, and there are problems of waste of silver resources and uneven coating.

Method used

The cold spraying process is used to spray the silver composite coating on the substrate surface of the high-current bus connection terminal, with a number of layers of 3-10, containing silver powder and composite transition element nanoparticles. A dense oxidation film is formed through the ligand effect of palladium/gold nanoparticles to prevent sulfide penetration, and the density and conductive properties of the coating are improved through shot peening.

Benefits of technology

The anti-sulfurization corrosion of the silver layer is achieved, the conductive properties are maintained, the current impedance is increased due to uneven coating, and the wear resistance and density of the silver layer are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-current bus connection terminal and a preparation method thereof, the high-current bus connection terminal comprises a substrate and a silver composite coating, the number of layers of the silver composite coating is 3-10, the thickness of the silver composite coating is 0.5-2mm, and raw materials comprise silver powder and / or composite transition element nanoparticles; the composite transition element nano-particles are palladium / gold nano-particles, and the mass ratio of the composite transition element nano-particles is in an equal difference increasing trend from the inner layer to the outer layer. According to the invention, the silver composite coating is sprayed on the surface of the base body of the connecting terminal, so that the penetration of sulfide can be effectively prevented, and the approaching of corrosive gases such as H2S and the like is repelled, thereby playing a role in preventing sulfuration corrosion; and the adopted cold spraying process has the advantages of being low in process temperature and small in heat input, workpiece thermal deformation and material structure damage cannot be caused, the material structure components are kept consistent, internal microstructures are arranged in order, and the conductivity and abrasion resistance of the silver layer can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment of electric power connectors, and in particular relates to a high-current busbar connection terminal and a preparation method thereof. Background Art

[0002] The high-current busbar is an important electrical connection component that is responsible for conducting large currents. The mechanical connection between the connection terminals plays an important role in conducting the electrical circuit. In order to improve the conductivity and reduce the contact resistance, a silver layer is usually prepared on the surface of the connection terminals.

[0003] Although the silver layer on the surface of the high-current busbar connection terminal has excellent conductive properties and can efficiently conduct electrical energy, the conductivity of the high-current busbar prepared by silver plating is as high as 101% IACS. However, when the connection terminal is exposed to the atmospheric environment, the surface is easily transformed from silver to light yellow, brown, or even a black film layer depending on the degree of corrosion. The discoloration of the silver surface not only affects its appearance quality, but also increases the contact resistance of the connection terminal and reduces the electrical performance.

[0004] There are many external environmental factors that cause silver to change color, including oxides (oxygen, nitrogen, chlorine elements), sulfides, residual salts, temperature, humidity, etc. Among them, Ag2O and AgO generated after oxidation are both black; when sulfides and sulfur oxides exist in the air, the final reaction product is a black Ag2S film layer. The presence of silver oxides and sulfides causes a significant decrease in conductivity, which leads to an increase in the contact resistance of the hardware terminals, thus affecting the efficiency and stability of power transmission and distribution.

[0005] CN110042389B discloses a process for laser cladding silver layer on the surface of high-current aluminum busbar hardware terminals. The invention uses laser as a heat source and adopts a reasonable laser energy density to melt the surface of an aluminum alloy workpiece, effectively forming a molten pool without being vaporized, and silver powder is fed into the molten pool as a raw material through a powder feeding device, melted and quickly cooled, and the silver layer solidifies on the surface of the workpiece. The cladding silver layer and the substrate of the workpiece are metallurgically bonded, which can greatly improve the performance of the substrate and form a dense and uniformly thick silver coating on the surface of the workpiece; when the surface of the coating is severely sulfided, the surface sulfided layer is removed by conventional hand-held polishing means, and the silver layer is exposed for continued use.

[0006] CN101503798B discloses a silver-plated anti-discoloration protective agent composition, which improves its anti-sulfurization and wear resistance by forming a protective complex film on the silver surface, and is mainly used for preventing discoloration of electronic components after silver plating. CN114910679B discloses a sulfide-resistant silver-based electrical contact material and a preparation method thereof, which adopts a silver-titanium-copper-vanadium alloy material and is prepared by cold isostatic pressing and sintering. The prepared silver-based electrical contact material has excellent anti-sulfurization discoloration ability.

[0007] In the prior art, the silver layer desulfurization method cannot have both the anti-sulfurization and conductive properties of the hardware terminal. In addition, due to the structure, volume and application environment of the high-current busbar connection terminal, the existing cold isostatic pressing, sintering and other processes cannot meet its needs. In addition, the laser cladding process may also cause deformation and coating oxidation, and polishing to remove the sulfide layer is subject to more restrictions and involves the waste of silver resources. Therefore, it is necessary to provide a connection terminal with a silver layer that can have both anti-sulfurization and conductive properties, and the preparation method of the silver layer is not affected by the structure, volume and environment. Summary of the invention

[0008] In view of the above technical problems, the present invention provides a high-current busbar connecting terminal and a preparation method thereof. A silver composite coating is sprayed on the surface of the connecting terminal substrate, which can effectively prevent the penetration of sulfides and repel the approach of corrosive gases such as H2S, thereby playing a role in preventing sulfide corrosion; and the cold spraying process adopted has the advantages of low process temperature and low heat input, which will not cause thermal deformation of the workpiece or damage to the material structure, and keeps the material structure composition consistent and the internal microstructure arranged in an orderly manner, which helps to improve the conductivity and wear resistance of the silver layer.

[0009] In order to achieve the above object, the present invention provides a high-current busbar connecting terminal, which includes a substrate and a coating, wherein the coating is a silver composite coating; the number of layers of the silver composite coating is 3-10 and the thickness is 0.5-2 mm.

[0010] Preferably, the silver coating comprises silver powder and composite transition element nanoparticles; the particle size of the silver powder is 1-50 μm, and the particle size of the composite transition element nanoparticles is 20 nm-10 μm.

[0011] Further preferably, the composite transition element nanoparticles are palladium / gold nanoparticles.

[0012] More preferably, the mass ratio of palladium to gold in the palladium / gold nanoparticles is 1:1.

[0013] More preferably, the composite transition element nanoparticles also contain one or more of scandium and yttrium.

[0014] Preferably, the first layer of the silver composite coating is a pure silver coating with a purity of ≥99.99%; The 2nd to 10th layers are silver and composite transition element nanoparticles, wherein the mass of the composite transition element nanoparticles accounts for 0.5-10% of the mass of the layer.

[0015] Further preferably, the mass of the composite transition element nanoparticles in the 2nd to 10th layers increases arithmetic progression with the number of layers, and the increment between two adjacent layers of the silver composite coating is 0.25%.

[0016] Further preferably, the thickness of the first layer is ≥0.5 mm; the thickness of the 2nd to 10th layers is ≤0.15 mm, and the thickness difference between two adjacent layers of the silver composite coating is ≤50 μm.

[0017] The present invention also provides a method for preparing a high-current busbar connecting terminal, comprising the following steps: S1. Pretreatment of the substrate of high current busbar connection terminal; S2, cold spraying silver powder onto the surface of the substrate to prepare a first silver layer; S3, mixing silver powder and composite transition element nanoparticles, and cold spraying them onto the surface of the substrate to prepare a second silver layer; S4, shot peening; S5. Repeat steps S3 and S4 to prepare a high-current busbar connection terminal with a silver composite coating.

[0018] Preferably, the pretreatment in step S1 is grinding or polishing.

[0019] Preferably, the process parameters of the cold spraying described in steps S2 and S3 are: the working gas is one or more of air, nitrogen or helium; the gas velocity is 300-1200m / s; the spray pressure is 1-7.5MPa; the spray temperature is 100-1000°C; and the spray distance is 5-80mm.

[0020] More preferably, the spraying temperature is 100-600° C. and the spraying distance is 5-80 mm.

[0021] Preferably, the shot peening in step S4 is spraying strengthening shots; the strengthening shots are one or a combination of steel shots, cast iron shots, glass shots, and ceramic shots.

[0022] Further preferably, the shot peening process is any one of pneumatic shot peening, centrifugal shot peening, microparticle shot peening, vibration shot peening or cold spray shot peening.

[0023] Preferably, step S4 further includes cleaning after shot peening, and the processing steps are as follows: (1) Use anhydrous acetone to clean the high-current busbar connection terminals after shot peening; (2) Use a soft brush to gently brush the high-current busbar connection terminals to remove the shot peening particles remaining on the surface; (3) Rinse again with acetone and evaporate to dryness.

[0024] The beneficial effects of the present invention are: 1. Due to the metal alloying effect caused by the ligand effect, synergistic effect, induced electron effect, etc. of silver and palladium / gold nanoparticles, the external silver layer can chemically adsorb oxygen. On the one hand, it can form a dense oxide film, which can effectively prevent the penetration of sulfides, thereby playing a role in preventing sulfide corrosion; on the other hand, from the perspective of gas, oxygen can preferentially contact and adsorb on the surface of the coating compared to sulfides, thereby repelling the approach of corrosive gases such as H2S, achieving the effect of anti-sulfurization, and can also effectively promote high conductivity.

[0025] 2. The cold spraying process adopted in the present invention has the advantages of low process temperature and low heat input, which will not cause thermal deformation of the workpiece or damage to the material structure, and keep the material structure composition consistent and the internal microstructure arranged in an orderly manner, thereby effectively avoiding the increase in current impedance caused by the unevenness of the coating; in addition, the residual stress in the cold spray coating is small and is compressive stress. The compressive stress makes it easier for electrons to move in the material, reducing the resistivity, thereby making the resistance smaller, which helps to improve the conductive performance of the silver layer.

[0026] 3. Spraying reinforcement pills on the surface of the cold-sprayed silver layer helps to refine the grains and reduce the porosity of the coating. Spraying reinforcement pills makes the coating denser, prevents the penetration and corrosion of sulfide molecules, and can effectively improve the conductivity and wear resistance of the silver layer.

[0027] 4. The composition of the silver composite coating changes arithmetic from the inner layer to the outer layer, which helps to ensure the uniformity of the overall composition structure of the hardware terminal, effectively prevents excessive local current density caused by component imbalance, and effectively avoids corrosion or damage caused by excessive local current density, thereby effectively ensuring the conductive properties of the substrate and the silver layer. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further explained below in conjunction with specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be construed as limiting the present invention. The protection scope of the present invention shall be subject to the contents recorded in the claims. Any modification or replacement made by a person skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.

[0029] In some embodiments of the present invention, the palladium / gold nanoparticles are spherical, rod-shaped, polyhedral, star-shaped, or nanoflower-shaped; the palladium / gold nanoparticles may be a core-shell structure or an alloy structure.

[0030] In some embodiments of the present invention, the thickness of the first silver layer is ≥0.5 mm, such as 0.5 mm, 1 mm, 1.5 mm, or 2 mm.

[0031] In some embodiments of the present invention, the thickness of the 2nd to 10th silver layers is ≤0.15 mm, such as 0.15 mm, 0.10 mm, or 0.05 mm; and the thickness difference between two adjacent layers of the silver composite coating is ≤50 μm, such as 50 μm, 40 μm, 30 μm, 20 μm, or 10 μm.

[0032] In some embodiments of the present invention, the first layer of silver composite coating is composed of pure silver, and the purity of the silver composite coating is ≥99.99%; the second to tenth layers of silver composite coating are composed of silver and palladium / gold nanoparticles, the mass proportion of palladium / gold nanoparticles in the second layer is 0.25%, the mass proportion of palladium / gold nanoparticles in the second to tenth layers is arithmetically increased, and the increment between two adjacent layers of silver composite coating is 0.5%-1.0%, and the mass proportion of palladium / gold nanoparticles in the tenth layer is ≤10%; taking an increment of 0.5% as an example, the second layer is 0.25%, the third layer is 0.75%, the fourth layer is 1.25%, the fifth layer is 1.75%... and the tenth layer is 4.25%.

[0033] In some embodiments of the present invention, reinforcing shots are sprayed on the surface of each silver layer, and the reinforcing shots are one or a combination of steel shots, cast iron shots, glass shots, and ceramic shots. Using shots to bombard the surface of the workpiece and implant residual compressive stress helps to improve the mechanical strength, wear resistance, fatigue resistance, and corrosion resistance of the parts. For example, if a silver layer with a thickness of 0.8 mm is sprayed, the thickness of the coating layer becomes 0.5 mm after spraying the reinforcing shots. Therefore, shot peening can increase the density, thereby improving the anti-sulfurization performance.

[0034] In some embodiments of the present invention, the shot peening process is one of pneumatic shot peening, centrifugal shot peening, microparticle shot peening or vibration shot peening.

[0035] In some embodiments of the present invention, the shot peening is spray-reinforced shot, and the reinforced shot is one or a combination of steel shot, cast iron shot, glass shot, and ceramic shot.

[0036] In some embodiments of the present invention, the parameters of the cold spraying process are: the working gas is one or more of air, nitrogen or helium; the spraying pressure of cold spraying is 1-7.5MPa, such as 1MPa, 2.5MPa, 5MPa, 7.5MPa; the spraying temperature of cold spraying is 100-600°C, such as 100°C, 250°C, 500°C, 750°C, 1000°C; the gas velocity of cold spraying is 300-1200m / s, such as 300m / s, 350m / s, 550m / s, 800m / s, 1000m / s, 1200m / s; the spraying distance of cold spraying is 5-80mm, such as 5mm, 25mm, 50mm, 70mm, 80mm.

[0037] In some embodiments of the present invention, a cold spraying process is used to spray the reinforcement pills, and the cold spraying process parameters for spraying the reinforcement pills are: the spraying pressure of the cold spraying is 1-7.5MPa (, such as 1MPa, 2.5MPa, 5MPa, 7.5MPa; the spraying temperature of the cold spraying is 100-1000°C, such as 100°C, 250°C, 500°C, 750°C, 1000°C; the gas velocity of the cold spraying is 300-1200m / s, such as 300m / s, 350m / s, 550m / s, 800m / s, 1000m / s, 1200m / s; the spraying distance of the cold spraying is 20-80mm, such as 20mm, 30mm, 40mm, 50mm, 60mm, 80mm.

[0038] Example 1 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is 3, wherein the substrate is a high-current aluminum busbar hardware terminal; the preparation method is as follows: S1. Manually polish the connection terminal substrate to remove surface oxides to ensure that the substrate aluminum alloy material is exposed on the workpiece surface, and use acetone to clean the area to be sprayed with the silver layer to remove residual oil on the surface; S2. Using silver powder as raw material, a first silver layer is prepared on the surface of the substrate by cold spraying process, with a purity of 99.99% and a thickness of 0.5 mm; the parameters of the cold spraying process are: the working gas is air, the spraying pressure is 4.5 MPa, the spraying temperature is 150°C, the gas velocity is 400 m / s, and the spraying distance is 55 mm; the particle size of the silver powder is 30 μm; S3, using a mixture of silver powder and palladium / gold nanoparticle powder as raw materials, and preparing a second silver layer on the surface of the substrate by cold spraying process; wherein the mass of the palladium / gold nanoparticle powder in the second silver layer accounts for 0.25% of the mass of the mixture, and the thickness is 0.1 mm; wherein the particle size of the silver powder is 30 μm, the particle size of the palladium / gold nanoparticle powder is 50 nm, and the mass ratio of palladium to gold nanoparticles is 1:1; S4, performing shot peening treatment on the surface of the second silver layer, wherein the shot peening process is pneumatic shot peening, and silicon carbide shots with a diameter of 1.5 mm are used for shot peening; S5, cleaning the high-current busbar connection terminal obtained in step S4 with acetone, then brushing it lightly with a soft brush to remove the remaining shot peening particles, and then cleaning it again with acetone; S6. After cleaning, repeat steps S3 and S4 to prepare a third silver layer, wherein the mass of the palladium / gold nanoparticle powder in the third silver layer accounts for 0.75% of the mass of the mixture and the thickness is 0.1 mm.

[0039] Example 2 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is 6; the preparation method and steps are the same as those in Example 1, except that the thickness of the 6 silver layers and the proportion of raw materials are different, as follows: Layer 1: The raw material is silver, the purity is 99.99%, and the thickness is 1mm; Layer 2: The raw materials are 99.75% silver and 0.25% palladium / gold nanoparticles, with a thickness of 0.15mm; Layer 3: Raw materials are 98.75% silver and 1.25% palladium / gold nanoparticles, with a thickness of 0.15 mm; Layer 4: Raw materials are 97.75% silver and 2.25% palladium / gold nanoparticles, with a thickness of 0.15 mm; Layer 5: The raw materials are 96.75% silver and 3.25% palladium / gold nanoparticles, with a thickness of 0.15mm; Layer 6: Raw materials are 95.75% silver and 4.25% palladium / gold nanoparticles, with a thickness of 0.17mm.

[0040] The particle size of the silver powder is 30 μm, the particle size of the palladium / gold nanoparticle powder is 50 nm, and the mass ratio of palladium to gold nanoparticles is 1:1.

[0041] Example 3 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is 9; the preparation method and steps are the same as those in Example 1, and the thickness of the 10 silver layers, the proportion of raw materials, and the cold spraying process are different, as follows: Layer 1: The raw material is silver, the purity is 99.99%, and the thickness is 1.5mm; Layer 2: The raw materials are 99.75% silver and 0.25% palladium / gold nanoparticles, with a thickness of 0.05mm; Layer 3: The raw materials are 99.25% silver and 0.75% palladium / gold nanoparticles, with a thickness of 0.05mm; Layer 4: The raw materials are 98.75% silver and 1.25% palladium / gold nanoparticles, with a thickness of 0.05mm; Layer 5: The raw materials are 98.25% silver and 1.75% palladium / gold nanoparticles, with a thickness of 0.05mm; Layer 6: Raw materials are 97.25% silver and 2.25% palladium / gold nanoparticles, with a thickness of 0.05mm; Layer 7: The raw materials are 97.25% silver and 2.75% palladium / gold nanoparticles, with a thickness of 0.07mm; Layer 8: The raw materials are 96.75% silver and 3.25% palladium / gold nanoparticles, with a thickness of 0.05mm; The 9th layer: the raw materials are 96.25% silver and 3.75% palladium / gold nanoparticles, with a thickness of 0.05mm; Layer 10: The raw materials are 95.75% silver and 4.25% palladium / gold nanoparticles, with a thickness of 0.08mm; The particle size of the silver powder is 50 μm, the particle size of the palladium / gold nanoparticle powder is 50 nm, and the mass ratio of palladium to gold nanoparticles is 1:1; The process parameters of cold spraying are: working gas is nitrogen, spray pressure is 5MPa, spray temperature is 250℃, gas velocity is 700m / s, and spray distance is 30mm.

[0042] Example 4 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is 10; the preparation method and steps are the same as those in Example 1, wherein the thickness of the 10 silver layers, the proportion of raw materials, and the cold spraying process are different, as follows: Layer 1: The raw material is silver, the purity is 99.99%, and the thickness is 0.5mm; Layer 2: The raw materials are 98% silver and 2% palladium / gold nanoparticles, with a thickness of 0.1mm; Layer 3: The raw materials are 97% silver and 3% palladium / gold nanoparticles, with a thickness of 0.12mm; Layer 4: Raw materials are 96% silver and 4% palladium / gold nanoparticles, thickness is 0.1mm; Layer 5: The raw materials are 95% silver and 5% palladium / gold nanoparticles, with a thickness of 0.12mm; Layer 6: Raw materials are 94% silver and 6% palladium / gold nanoparticles, thickness is 0.1mm; Layer 7: The raw materials are 93% silver and 7% palladium / gold nanoparticles, with a thickness of 0.12mm; Layer 8: Raw materials are 92% silver and 8% palladium / gold nanoparticles, thickness is 0.1mm; Layer 9: The raw materials are 91% silver and 9% palladium / gold nanoparticles, with a thickness of 0.12mm; The 10th layer: The raw materials are 90% silver and 10% palladium / gold nanoparticles, with a thickness of 0.1mm; The particle size of the silver powder is 1 μm, and the particle size of the palladium / gold nanoparticle powder is 20 nm; The process parameters of cold spraying are: working gas is helium, spray pressure is 1MPa, spray temperature is 100℃, gas velocity is 300m / s, and spray distance is 5mm.

[0043] Example 5 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is three; the preparation method and steps are the same as those in Example 1, wherein the thickness of the three silver layers, the proportion of raw materials, and the cold spraying process are different, as follows: Layer 1: The raw material is silver, the purity is 99.99%, and the thickness is 1.5mm; The second layer: the raw materials are 99.5% silver and 0.5% palladium / gold nanoparticles, with a thickness of 0.15mm; Layer 3: The raw materials are 99.25% silver and 0.75% palladium / gold nanoparticles, with a thickness of 0.19 mm; The particle size of the silver powder is 50 μm, and the particle size of the palladium / gold nanoparticle powder is 500 nm; The process parameters of cold spraying are: working gas is helium, spray pressure is 7.5MPa, spray temperature is 1000℃, gas velocity is 1200m / s, and spray distance is 80mm.

[0044] Comparative Example 1 A high-current busbar connection terminal comprises a substrate and a coating, wherein the coating is a silver-copper alloy, wherein the substrate is a high-current aluminum busbar hardware terminal, and the preparation method is as follows: S1. Pre-treat the surface of the high-current aluminum busbar hardware terminal, manually polish and remove the surface oxide to ensure that the base aluminum alloy material is exposed on the workpiece surface; S2. Use acetone to clean the area to be coated to remove residual oil on the surface; S3. Use laser cladding equipment to clad the silver-copper alloy on the surface of the high-current aluminum busbar hardware terminal; the mass ratio of silver to copper in the silver-copper alloy is 9:1, the particle size is 100μm, the thickness is 1.5mm, and the cladding process parameters are: spot size is Φ3, powder feed rate is 100g / min, defocus amount is 3mm, working gas is argon, and the argon flow rate is 20L / min.

[0045] Comparative Example 2 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is two; the preparation method and steps are the same as those in Example 1, except that the thickness of the two silver layers and the proportion of raw materials are different, as follows: Layer 1: The raw material is silver, the purity is 99.99%, and the thickness is 0.5mm; Layer 2: Raw materials are 99.75% silver and 0.25% palladium / gold nanoparticles, with a thickness of 0.1mm.

[0046] Comparative Example 3 A high-current busbar connection terminal comprises a substrate and a silver coating, wherein the raw materials of the silver coating are 99.75% silver and 0.25% palladium / gold nanoparticles, the thickness is 0.7 mm, and the preparation method and steps are the same as those in Example 1.

[0047] Comparative Example 4 A high-current busbar connection terminal, the number of layers and raw materials of the silver composite coating are the same as those in Example 1, only laser cladding is used during preparation, and the process parameters are: spot size is Φ4, powder feeding amount is 120g / min, defocus amount is 4mm, working gas is argon, and the flow rate of argon is 15L / min.

[0048] Comparative Example 5 A high-current busbar connection terminal, the number of layers, raw materials and preparation method of the silver composite coating are the same as those in Example 1, and only steps S4 and S5 are omitted.

[0049] Comparative Example 6 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is three; the preparation method and steps are the same as those in Example 1, except that the proportion of raw materials of the three silver layers is different, as follows: Layer 1: The raw material is silver, the purity is 99.99%, and the thickness is 0.5mm; Layer 2: The raw materials are 99.9% silver and 0.1% palladium / gold nanoparticles, with a thickness of 0.1mm; Layer 3: Raw materials are 99.8% silver and 0.2% palladium / gold nanoparticles, with a thickness of 0.1mm.

[0050] Comparative Example 7 A high-current busbar connection terminal, the number of layers of the silver composite coating and the preparation method are the same as those in Example 1, and the palladium / gold nanoparticle powder is replaced by an equal amount of palladium nanoparticle powder with the same particle size.

[0051] Comparative Example 8 A high-current busbar connection terminal, the number of layers of the silver composite coating and the preparation method are the same as those in Example 1, and the palladium / gold nanoparticle powder is replaced by an equal amount of gold nanoparticle powder with the same particle size.

[0052] Comparative Example 9 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is three; the preparation method and steps are the same as those in Example 1, except that the thickness of the three silver layers is different, as follows: Layer 1: The raw material is silver, the purity is 99.99%, and the thickness is 0.5mm; Layer 2: The raw materials are 99.75% silver and 0.25% palladium / gold nanoparticles, with a thickness of 0.2mm; Layer 3: Raw materials are 99.5% silver and 0.5% palladium / gold nanoparticles, with a thickness of 0.2mm.

[0053] Comparative Example 10 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is 3; the preparation method and steps are the same as those in Example 1, except that the content of palladium / gold nanoparticles in the second and third layers is different, as follows: Layer 1: The raw material is silver, the purity is 99.99%, and the thickness is 0.5mm; Layer 2: The raw materials are 99.75% silver and 1.2% palladium / gold nanoparticles, with a thickness of 0.1mm; Layer 3: Raw materials are 99.5% silver and 2.4% palladium / gold nanoparticles, with a thickness of 0.1mm.

[0054] Comparative Example 11 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is 3; the preparation method and steps are the same as those in Example 1, except that the mass ratio of the adjacent two layers of palladium / gold is not changed, which is specifically as follows: Layer 1: The raw material is silver, the purity is 99.99%, and the thickness is 0.5mm; Layer 2: The raw materials are 99.75% silver and 0.25% palladium / gold nanoparticles, with a thickness of 0.1mm; Layer 3: Raw materials are 99.75% silver and 0.25% palladium / gold nanoparticles, with a thickness of 0.1mm.

[0055] Comparative Example 12 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is 3; the preparation method and steps are the same as those in Example 1, except that the mass ratio of palladium to gold in the palladium / gold nanoparticle powder is changed to 2:1.

[0056] Comparative Example 13 A high-current busbar connection terminal comprises a substrate and a silver composite coating, wherein the number of layers of the silver composite coating is 3; the preparation method and steps are the same as those in Example 1, except that the mass ratio of palladium to gold in the palladium / gold nanoparticle powder is changed to 1:2.

[0057] Results: The connection terminals prepared in the above embodiments and comparative examples were tested for their anti-sulfurization performance, electrical conductivity and density. The testing method is as follows. The test results are shown in the table below. (1) Anti-sulfurization performance test: refer to the test provisions in the national standard "Sulfur dioxide corrosion test of metals and other inorganic coatings under normal condensation conditions" (GB / T 9789-2008). The test method is to continuously expose in the test chamber, observe the appearance of corrosion points, and record the test time before the first corrosion point appears. The longer the time, the better the sample's resistance to sulfur dioxide corrosion.

[0058] (2) Conductivity test: The conductivity of the silver coating is tested using an eddy current conductivity meter at 20℃±5℃, with reference to GB / T 32971-2016 Eddy current test method for electrical conductivity of copper and copper alloys. The test method is to measure the electrical conductivity of non-ferrous metals using an eddy current conductivity meter. This method uses an alternating current coil (probe) close to the surface of a conductive material. Under the action of the alternating magnetic field of the coil, vortex currents (eddy currents) are induced on the surface and near the surface of the material. These eddy currents generate their own magnetic fields to react to the coils, and the magnitude of the reaction is related to the conductivity of the surface and near the surface of the material. The conductivity of non-ferromagnetic conductive materials can be directly detected using an eddy current conductivity meter.

[0059] (3) Density test: Determined by metallographic examination, the test method is to cut, inlay and polish the sample along the cross section. If necessary, the sample can be treated with a suitable corrosive agent, and the microstructure of the deposit can be observed by an optical microscope or an electron microscope at a suitable magnification, and the density can be determined by calculating the area ratio of the holes.

[0060]

[0061] It can be seen from the above table that the first corrosion of the high-current busbar connection terminal containing the silver composite coating prepared in Examples 1-5 occurs at about 2000 hours, the conductivity is maintained at 100 IACS%, and the density is above 99.8%. When the number of layers of the silver composite coating is changed to 2 layers (Comparative Example 2) or 1 layer (Comparative Example 3), its corrosion resistance, conductivity and density are significantly reduced.

Claims

1. A high current busbar connection terminal, characterized in that: The connecting terminal comprises a substrate and a coating, wherein the coating is a silver composite coating; the number of layers of the silver composite coating is 3-10 and the thickness is 0.5-2 mm.

2. A high current busbar connection terminal according to claim 1, characterized in that: The silver composite coating comprises silver powder and / or composite transition element nanoparticles; the particle size of the silver powder is 1-50 μm, and the particle size of the composite transition element nanoparticles is 20 nm-10 μm.

3. A high current busbar connection terminal according to claim 2, characterized in that: The composite transition element nanoparticles are palladium / gold nanoparticles.

4. A high current busbar connection terminal according to claim 3, characterized in that: The mass ratio of palladium to gold in the palladium / gold nanoparticles is 1:

1.

5. A high current busbar connection terminal according to claim 1, characterized in that: The first layer of the silver composite coating is a pure silver coating with a purity of ≥99.99%; The 2nd to 10th layers are silver and composite transition element nanoparticles, wherein the mass of the composite transition element nanoparticles accounts for 0.25-10% of the mass of the layer.

6. A high current busbar connection terminal according to claim 5, characterized in that: The mass of the composite transition element nanoparticles in the 2nd to 10th layers increases arithmetic progression as the number of layers increases, and the increment between two adjacent layers of the silver composite coating is 0.5-1.0%.

7. A high current busbar connection terminal according to claim 5, characterized in that: The thickness of the first layer is ≥0.5 mm; the thickness of the 2nd to 10th layers is ≤0.15 mm, and the thickness difference between two adjacent layers of silver composite coating is ≤50 μm.

8. A method for preparing a high-current busbar connecting terminal according to any one of claims 1 to 7, characterized in that: The steps include: S1. Pretreatment of the substrate of high current busbar connection terminal; S2, cold spraying silver powder onto the surface of the substrate to prepare a first silver layer; S3, mixing silver powder and composite transition element nanoparticles, and cold spraying them onto the surface of the substrate to prepare a second silver layer; S4, shot peening; S5. Repeat steps S3 and S4 to prepare a high-current busbar connection terminal with a silver composite coating.

9. The preparation method according to claim 8, characterized in that: The pretreatment in step S1 is grinding or polishing; The process parameters of the cold spraying in steps S2 and S3 are: the working gas is one or more of air, nitrogen or helium; the gas velocity is 300-1200 m / s; the spray pressure is 1-7.5 MPa; the spray temperature is 100-1000° C.; the spray distance is 5-80 mm; The shot peening in step S4 is spraying strengthening shots; the strengthening shots are one or a combination of steel shots, cast iron shots, glass shots, and ceramic shots.

10. The preparation method according to claim 8, characterized in that: Step S4 also includes cleaning after shot peening, and the processing steps are as follows: (1) Acetone cleaning; (2) Soft brush treatment to remove shot peening particles; (3) Acetone cleaning.

Citation Information

Patent Citations

  • Silver plating anti-color changing protecting agent composition

    CN101503798B

  • Laser cladding silver layer process for high current aluminum busbar hardware terminals

    CN110042389B

  • Wireless communication electric energy meter with electricity utilization information acquisition function and method

    CN114910679A